The Relationship between Work Stress and Metabolic Syndrome with the Mediation of Emotional Eating and Mood Disturbances Among Mining Workers - Septa Indra Puspikawati; Atmaka, S.Gz, MPH, Dominikus Raditya; Shintia Yunita Arini; Bian Shabri Putri Irwanto; Asri Meidyah Agustin; Miko Ardiansyah; Erni Astutik; Eka Cahya Febriyanto (Media Gizi Indonesia, 2026)
The prevalence of metabolic syndrome is increasing globally due to various factors that influence the progression of this syndrome. Identifying the factors that influence the development of metabolic syndrome is important, especially among working populations. This study aimed to explore the association between job-related stress and metabolic syndrome in mining workers, with emotional eating and mood disorders as mediating factors. An observational analytic method with a cross-sectional study design was employed. The research subjects were 131 workers from a mining contractor company in East Kalimantan, who were chosen after the research objectives were explained and their informed consent was obtained. The independent variable examined was work stress, and the dependent variable was metabolic syndrome. Emotional eating and mood disturbances were included as mediating variables in the analysis. Data were collected through measurements and questionnaire completion. The data were analyzed using path analysis techniques, and SPSS version 26 was used for statistical processing. The results showed that there was no relationship between work stress and metabolic syndrome mediated by emotional eating and mood disturbances. However, a relationship was found between work stress and the mediator variables of emotional eating and mood disturbances.